2020
DOI: 10.1155/2020/4517587
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cathepsins in Innate and Adaptive Immune Responses in Periodontitis

Abstract: Periodontitis is an infectious disease whereby the chronic inflammatory process of the periodontium stimulated by bacterial products induces specific host cell responses. The activation of the host cell immune system upregulates the production of inflammatory mediators, comprising cytokines and proteolytic enzymes, which contribute to inflammation and bone destruction. It has been well known that periodontitis is related to systemic inflammation which links to numerous systemic diseases, including diabetes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 121 publications
0
18
0
Order By: Relevance
“…Here, we revealed that Dg-Cys is expressed in the midgut and ovaries, but not in the salivary glands of PRMs, suggesting that it plays important roles in blood digestion and embryogenesis. In addition, recombinant Dg-Cys-his inhibited the enzymatic activities of cathepsins L and S, which mediate innate immunity and antigen processing [34,35], suggesting that it might be associated with the modulation of host immunity. In contrast, consistent with previous reports of several cystatins [13,15,36], Dg-Cys did not interrupt the enzymatic activity of cathepsin B, thus indicating the selectivity and/or specificity of Dg-Cys against its target cysteine proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we revealed that Dg-Cys is expressed in the midgut and ovaries, but not in the salivary glands of PRMs, suggesting that it plays important roles in blood digestion and embryogenesis. In addition, recombinant Dg-Cys-his inhibited the enzymatic activities of cathepsins L and S, which mediate innate immunity and antigen processing [34,35], suggesting that it might be associated with the modulation of host immunity. In contrast, consistent with previous reports of several cystatins [13,15,36], Dg-Cys did not interrupt the enzymatic activity of cathepsin B, thus indicating the selectivity and/or specificity of Dg-Cys against its target cysteine proteases.…”
Section: Discussionmentioning
confidence: 99%
“…The early symptoms of this disease are not obvious, but with the progress of the disease, there may occur loosening and shedding of teeth, soft tissue inflammation, alveolar bone absorption, and other symptoms. Some patients have developed into severe periodontitis [ 2 ]. According to the research survey, in 2010, the incidence of severe periodontitis was about 11% among people over 15 years old in the world, the incidence of severe periodontitis was about 12.1%–16.1% in China, and the incidence increased with the increase in age and ranking sixth among the global epidemic diseases [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…antigen presentation pathways can promote one another, due to similar processing of ligands/antigens within endosomal cellular compartments (61)(62)(63). MHC class II antigen processing and presentation is a critical pathway for professional antigen-presenting cells, such as B-cells, macrophages, and dendritic cells (DCs), to determine what antigens are self vs. foreign.…”
Section: Commensal Oral Microbiota Supports Dendritic Cell Upregulation Through Mhc Class II Associated Genes In Alveolar Bone Marrow Repmentioning
confidence: 99%